PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA KESUSILAAN DALAM HUKUM PIDANA POSITIF SAAT INI - Sri Endah Wahyuningsih (UNISSULA, 2016)
Problems of sexual offenses against children arising from the enforcement of the criminal law has not been oriented to the protection of victims, especially justice, but rather on the application of penalties on the offender. As a result, not make people afraid of committing a crime of morality, even more perpetrators of rape and sexual abuse against children. the problem in this research is how the provisions of the legal protection of children as victims of sexual offenses under criminal law are positive today.Legal protection of child victims of crime in the criminal law of chastity positive current on Article 287, 290, 292, 293, 294 and 295 of the Criminal Code and Article 81 and 82 of the Act.No. 23/2002, as amended. Act. No. 35 of 2014 as amended by Government Regulation No.1 / 2016 on the amendment of the Law No. 23/2002 on Child Protection, and when the victims are included in the scope of the household, then apply the provisions of Articles 46 and 47 of the Law. No. 23/2004 on the Elimination of Domestic Violence, and Law No. 31/2014 on Witnessand Victim Protection. weakness that emerged in the Act. No. 31/2014 is the absence of a provision governing the sanctions when players do not give restitution to the victims.